In-Silico Study and Antioxidant Capacity from Jamaican Cherry, Red Ginger, Thyme Combination as Multi-target Nutraceutical for Chronic Obstructive Pulmonary Disease - Sayyidah Sayyidah; Nenden Nurhasanah; Nanang Yunarto; Lidya Pratiwi Afri Tjaja (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2026)
Chronic obstructive pulmonary disease (COPD) is one of the health concerns in Indonesia with 4.8 million people suffer from COPD. Global Adult Tobacco Survey Indonesia reported 70.2 million active smokers in 2021. This trend raises concerns about the future trajectory of COPD cases in the country. COPD is a chronic condition that impairs the lower respiratory system due to progressive stimuli that initiate oxidant-antioxidant imbalance contributes to dysregulated inflammation cascade response. Some natural ancient plants that had been used to relieve respiratory discomfort are Ginger (Zingiber officinale var.Rubrum) and Thyme (Thymus vulgaris). In order to give synergetic mechanism to imboost antioxidant capacity also mitigate COPD symptoms, this research combine both plants with Jamaican Cherry (Muntingia calabura) leave as a powder drink formulation. This study is conducted to analysis the potential of these combination through in-silico along with antioxidant capacity evaluation from each formulation. Total 75 compounds that meet Lipinski rules from the plants had been screened to identify the overlapping genes. Based on Network Pharmacology and validated with molecular docking analysis the potential targets based on the best degree value were IL-8(-11.2 kcal/mol), TNF-α (-8.9 kcal/mol), MMP-9(-7.7 kcal/mol) and IL-6(-7 kcal/mol). The highest binding affinity compound was 3’-hydroxydaidzein from Jamaican Cherry. The powder drink formulation made through wet granulation and antioxidant evaluated using DPPH(1,1-diphenyl-2-picrylhydrazyl) method. The antioxidant capacity was IC50 39.99 ppm; 36.10 ppm ; and 28.30 ppm for F1, F2 and F3 respectively compared to ascorbic acid 13.03 ppm. To conclude, this natural combination nutraceutical has potential as supportive natural remedy for COPD.